The OEIS Foundation is supported by donations from users of the OEIS and by a grant from the Simons Foundation.

 Hints (Greetings from The On-Line Encyclopedia of Integer Sequences!)
 A138247 E.g.f.: Sum_{n>=0} exp( (2^n+3^n)*x ) * (2^n+3^n)^n * x^n/n!. 7
 1, 7, 223, 49849, 94705663, 1616229320497, 251286598125520183, 357716675257916544062689, 4670472774542449929397808845183, 559006854195449142958954163012808059617, 612171730457531439763516750114999086563829844663, 6118056385739077528636842573416061383741677666682643900049 (list; graph; refs; listen; history; text; internal format)
 OFFSET 0,2 COMMENTS GENERAL BINOMIAL IDENTITY. When p=2, q=3, this sequence illustrates the following identity: Sum_{k=0..n} C(n,k)*(p^k + q^k)^n = Sum_{k=0..n} C(n,k)*(1 + p^(n-k)*q^k)^n which is a special case of the more general binomial identity: Sum_{k=0..n} C(n,k)*(s*p^k + t*q^k)^(n-k) * (u*p^k + v*q^k)^k = Sum_{k=0..n} C(n,k)*(s + u*p^(n-k)*q^k)^(n-k) * (t + v*p^(n-k)*q^k)^k. LINKS FORMULA E.g.f.: Sum_{n>=0} (2^n + 3^n)^n * exp( (2^n + 3^n)*x ) * x^n / n!. O.g.f.: Sum_{n>=0} (2^n + 3^n)^n * x^n / (1 - (2^n + 3^n)*x)^(n+1). - Paul D. Hanna, Jul 13 2019 FORMULAS FOR TERMS. a(n) = Sum_{k=0..n} C(n,k)*(2^k + 3^k)^n. a(n) = Sum_{k=0..n} C(n,k)*(1 + 2^(n-k)*3^k)^n. a(n) = Sum_{k=0..n} C(n,k)*A007689(k)^n. a(n) = Sum_{k=0..n} C(n,k)*A094617(n,k)^n. a(n) ~ 3^(n^2). - Vaclav Kotesovec, Jul 14 2019 EXAMPLE E.g.f.: A(x) = 1 + 7*x + 223*x^2/2! + 49849*x^3/3! + 94705663*x^4/4! + 1616229320497*x^5/5! + 251286598125520183*x^6/6! + 357716675257916544062689*x^7/7! + 4670472774542449929397808845183*x^8/8! + ... such that A(x) = exp(2*x) + (2+3)*exp((2+3)*x)*x + (2^2+3^2)^2*exp(2^2+3^2)*x)*x^2/2! + (2^3+3^3)^3*exp(2^3+3^3)*x)*x^3/3! + (2^4+3^4)^4*exp(2^4+3^4)*x)*x^4/4! + ... ORDINARY GENERATING FUNCTION. O.g.f.: B(x) = 1 + 7*x + 223*x^2 + 49849*x^3 + 94705663*x^4 + 1616229320497*x^5 + 251286598125520183*x^6 + 357716675257916544062689*x^7 + ... such that B(x) = 1/(1-2*x) + (2+3)*x/(1 - (2+3)*x)^2 + (2^2+3^2)^2*x^2/(1 - (2^2+3^2)*x)^3 + (2^3+3^3)^3*x^3/(1 - (2^3+3^3)*x)^4 + (2^4+3^4)^4*x^4/(1 - (2^4+3^4)*x)^5 + ... ILLUSTRATION OF TERMS. a(1) = 2 + 5 = 3 + 4 = 7 ; a(2) = 2^2 + 2*5^2 + 13^2 = 5^2 + 2*7^2 + 10^2 = 223 ; a(3) = 2^3 + 3*5^3 + 3*13^3 + 35^3 = 9^3 + 3*13^3 + 3*19^3 + 28^3 = 49849. MATHEMATICA Table[Sum[Binomial[n, k]*(2^k + 3^k)^n, {k, 0, n}], {n, 0, 12}] (* Vaclav Kotesovec, Jul 14 2019 *) PROG (PARI) {a(n)=local(p=2, q=3, s=1, t=1, u=1, v=1); sum(k=0, n, binomial(n, k)*(s*p^k + t*q^k)^(n-k)*(u*p^k + v*q^k)^k)} /* right side of the general binomial identity: */ {a(n)=local(p=2, q=3, s=1, t=1, u=1, v=1); sum(k=0, n, binomial(n, k)*(s + u*p^(n-k)*q^k)^(n-k) * (t + v*p^(n-k)*q^k)^k)} CROSSREFS Cf. A007689, A094617, A196457, A196458, A196459, A196460. Sequence in context: A202655 A009488 A302059 * A322709 A015506 A210099 Adjacent sequences:  A138244 A138245 A138246 * A138248 A138249 A138250 KEYWORD nonn AUTHOR Paul D. Hanna, Mar 09 2008, revised Mar 11 2008 STATUS approved

Lookup | Welcome | Wiki | Register | Music | Plot 2 | Demos | Index | Browse | More | WebCam
Contribute new seq. or comment | Format | Style Sheet | Transforms | Superseeker | Recent
The OEIS Community | Maintained by The OEIS Foundation Inc.

Last modified June 2 18:09 EDT 2020. Contains 334787 sequences. (Running on oeis4.)